Perioperative duloxetine for acute postoperative analgesia: a meta-analysis of randomized trials. Issue 10 (1st August 2019) - Zorrilla-Vaca, Andrés; Stone, Alexander; Caballero-Lozada, Andres Fabricio; Paredes, Stephania; Grant, Michael Conrad
Abstract : Background: Multimodal analgesia is a fundamental part of modern surgery and enhanced recovery pathways. Duloxetine, a serotonin and norepinephrine reuptake inhibitor, has been validated for the treatment of chronic neuropathic pain. The evidence for duloxetine as an adjunct for the treatment of acute postoperative pain remains controversial. We conducted a meta-analysis to determine the efficacy of duloxetine in the acute perioperative setting. Methods: A literature search was conducted in the major databases (PubMed, EMBASE and Google Scholar) for randomized controlled trials (RCTs) evaluating duloxetine compared with placebo control for acute postoperative pain. The primary outcome was postoperative pain assessed at 2, 4, 6, 24 and 48 hours time frames. Secondary outcomes included postoperative opioid administration, as well as side effects, such as postoperative nausea/vomiting (PONV), pruritus, dizziness and headache. Results: 574 patients (n=9 RCTs) were included in the analysis, divided between duloxetine (n=285 patients) and placebo (n=289 patients). Duloxetine use was associated with a significant reduction in pain scores as early as 4 (mean difference (MD) −0.9, 95% CI −1.33 to −0.47) and as late as 48 (MD −0.94, 95% CI −1.56 to −0.33) hours postoperatively compared with placebo. In addition, duloxetine was associated with a significant reduction in opioid administration at 24 (standardized MD (SMD) −2.24, 95% CI −4.28 to −0.19) and 48 (SMD −2.21, 95% CI −4.13 to −0.28) hours as well as a significant reduction in PONV (risk ratio 0.69, 95% CI 0.49 to 0.95, p=0.03) compared with placebo. There was no difference between groups in other side effects. Conclusion: Duloxetine, a non-opioid neuromodulator, may provide efficacy for the treatment of acute perioperative pain. Additional prospective studies are required to establish optimal perioperative dosing regimens, role in the setting of a comprehensive multimodal analgesic plan and impact on chronic postsurgical pain. PROSPERO registration number: CRD42019121416